Studies on the 2011 Off the Pacific Coast of Tohoku Earthquake - Kawase, Hiroshi (Natural Disaster Science and Mitigation Engineering: DPRI reports, 2014)
The Tohoku earthquake on March 11, 2011, officially designated the "Off the Pacific Coast of Tohoku, Japan Earthquake" by the Japan Meteorological Agency caused an unprecedentedly severe disaster in the northeastern part (Tohoku) of the Japanese island of Honshu. This first volume of the series Natural Disaster Science and Mitigation Engineering: DPRI Reports covers various aspects of investigations of scientific findings as well as issues related to the disaster and the subsequent evacuation necessitated by the earthquake. The series presents recent advances in natural disaster sciences and mitigation technologies developed in Japan, which will be valuable for the mitigation of disasters of a similar kind resulting from future events around the world.